Resolving the In‐Plane Anisotropic Properties of Black Phosphorus. Issue 6 (16th May 2017) - Liu, Xiaolong; Ryder, Christopher R.; Wells, Spencer A.; Hersam, Mark C.
Abstract : Two‐dimensional (2D) black phosphorus (BP) has recently attracted significant attention due to its favorable semiconducting properties and promise for nanoscale devices. Additionally, BP possesses distinctive anisotropic physical properties, which stem from the non‐equal bond angles and bond strengths in its crystal structure along its orthogonal in‐plane directions. Here, the anisotropic properties of BP are summarized, along with the methods to characterize them and the opportunities they present for novel technological applications. This survey of the progress in characterizing the anisotropy of BP will inform future efforts in BP and related anisotropic 2D nanomaterials. Abstract : Two‐dimensional (2D) black phosphorus (BP) displays high in‐plane anisotropy, which distinguishes it from other 2D materials. The experimental methods that can potentially characterize the structural, optical, vibrational, electronic, thermal, and mechanical anisotropic properties of BP are evaluated. As the prototypical anisotropic 2D material, the results pertaining to BP can likely be generalized to related anisotropic 2D materials in the future.